How Canadians Communicate VI: Food Promotion, Consumption, and Controversy - Edited by Charlene Elliott (Athabasca University Press, 2016)
Food nourishes the body, but our relationship with food extends far beyond our need for survival. Food choices not only express our personal tastes but also communicate a range of beliefs, values, affiliations and aspirations-sometimes to the exclusion of others. In the media sphere, the enormous amount of food-related advice provided by government agencies, advocacy groups, diet books, and so on compete with efforts on the part of the food industry to sell their product and to respond to a consumer-driven desire for convenience. As a result, the topic of food has grown fraught, engendering sometimes acrimonious debates about what we should eat, and why. By examining topics such as the values embedded in food marketing, the locavore movement, food tourism, dinner parties, food bank donations, the moral panic surrounding obesity, food crises, and fears about food safety, the contributors to this volume paint a rich, and sometimes unsettling portrait of how food is represented, regulated, and consumed in Canada. With chapters from leading scholars such as Ken Albala, Harvey Levenstein, Stephen Kline and Valerie Tarasuk, the volume also includes contributions from "food insiders"-bestselling cookbook author and food editor Elizabeth Baird and veteran restaurant reviewer John Gilchrist. The result is a timely and thought-provoking look at food as a system of communication through which Canadians articulate cultural identity, personal values, and social distinction.